Sotorasib for previously treated colorectal cancers with KRASG12C mutation (CodeBreaK100): a prespecified analysis of a single-arm, phase 2 trial. Issue 1 (January 2022) - Fakih, Marwan G; Kopetz, Scott; Kuboki, Yasutoshi; Kim, Tae Won; Munster, Pamela N; Krauss, John C; Falchook, Gerald S; Han, Sae-Won; Heinemann, Volker; Muro, Kei; Strickler, John H; Hong, David S; et al.
Summary: Background: Sotorasib, a specific, irreversible KRAS G12C protein inhibitor, has shown monotherapy clinical activity in KRAS G12C -mutated solid tumours, including colorectal cancer, in the CodeBreaK100 phase 1 trial. We aimed to investigate the activity and safety of sotorasib in phase 2 of the trial. Methods: In this single-arm, phase 2 trial, adult patients with KRAS G12C -mutated advanced solid tumours were enrolled, from 59 medical centres in 11 countries, if they were aged 18 years or older, had at least one measurable lesion according to the Response Evaluation Criteria in Solid Tumours (RECIST) version 1.1, and had an Eastern Cooperative Oncology Group performance status of 1 or lower. Only data for patients with colorectal cancer, enrolled at 33 medical centres in nine countries, are presented from this basket trial. To be enrolled, the patients had to have progressed after receiving fluoropyrimidine, oxaliplatin, and irinotecan treatment. These patients were administered 960 mg sotorasib orally once per day until disease progression, development of unacceptable side-effects, withdrawal of consent, or death. The primary endpoint was objective response (complete or partial response) as assessed by blinded independent central review. Response was evaluated in patients who received at least one dose of sotorasib and had at least one measurable lesion at baseline; safety was evaluated in patients who received at least one dose of sotorasib. This analysis is a prespecified analysis triggered by the phase 2 colorectal cancer cohort. This study is registered with ClinicalTrials.gov, NCT03600883, and is active but no longer recruiting. Findings: On March 1, 2021, at data cutoff, 62 patients with KRAS G12C -mutant colorectal cancer had been enrolled between Aug 14, 2019, and May 21, 2020, and had received at least one dose of sotorasib monotherapy. Objective response was observed in six (9·7%, 95% CI 3·6–19·9) of 62 patients, all with partial response. Treatment-related adverse events at grade 3 occurred in six (10%) patients, the most common of which was diarrhoea (two [3%] of 62 patients), and at grade 4 occurred in one (2%) patient (blood creatine phosphokinase increase); no fatal events were recorded. Serious treatment-related adverse events occurred in two (3%) patients (back pain and acute kidney injury). Interpretation: Although the 9·7% overall response rate did not reach the benchmark, oral administration of sotorasib once per day showed modest anti-tumour activity and manageable safety in these heavily pretreated chemorefractory patients. Sotorasib is under evaluation in combination with other therapeutics to increase potential activity and overcome potential resistance mechanisms. Funding: Amgen.